The North Harbor renewal project an eco-port waterfront development - Balingit, Ligaya Loribelle B.; Jose, Janet J.; Tirao, Candice A. (College of Architecture, University of the Philippines Diliman, 2000)
Technological civilization opened unlimited new vistas to man. It made possible cities larger than before, offering new benefits of urban life to ever greater number of men, and bringing a diversity of social life, cultural and intellectual exchange never before known. But now, in the center of most of these cities, malignant cores of decay have developed. The residents of city slums, and the existing development near waterfront know little of the rich variety of choice and quality that exalts human life. More frequently, their lives are encompassed by filth, ugliness and squalor. A worldwide concern for the present conditions of the world has been tremendous as it faces the new millennium. And all these concerns are undoubtedly focusing on the betterment of the lives of the people and consequently to the environment that they all live in. Thus, careful studies on needed redevelopments for different areas are being conducted. These studies give major considerations on achieving an all-round balance between such factors as industry, human life, and the environment. Since the end of World War II, large metropolitan regions everywhere have been permitted to grow so rapidly and with such lack of effective controls that many are now dangerously disorganized. Worldwide economic competition between metropolitan regions will necessarily stimulate and compel major improvements in their organization. Locally, demands for programs to meet social and environmental needs will be even more compelling. As a consequence, most of the large metropolitan regions of the world will be physically restructured and reshaped during the next half century. The city of Manila is one example of this. The rapid rural-urban migration following the post-war period saw a transformation of the city into a bustling metropolis. At present, the City has already launched the Urban Renewal Development Strategy and flagship programs which includes the development of almost the whole Manila Bay